Study the Effect of Lemon Extract on Some Types of Bacteria and Candida - Heyam G. Al Mousawi (American Journal of Botany and Bioengineering, 2026)
Extracts of Lemon had long been known for their antimicrobial activities, making Lemon a subject of interest in the scientific research. The current study deals with investigating the impacts of lemon peels extracts (ethanol and chloroform) on Staphylococcus aureus (S. aureus), Pseudomonas aeruginosa (P. aeruginosa), and Candida albicans (C. albicans), assessing their inhibitory effects via MIC, IC50 values, and optical densities (ODs) measurements. The phytochemical examination of lemon peels extract revealed that these peels have different bioactive compounds at different levels, the concentration of total polyphenol was 124 (mg/L), Flavonoids was at 150 (mg/L), Tannins level was 13 (mg/L), while alkaloids were found with low concentration at 5 (mg/L). The current findings indicate a strong inverse relationship between concentrations of Lemon peels extract and DPPH radical scavenging activity. As the concentration increases, the inhibition percentage escalated significantly, showing that greatest concentration of Lemon peels extract being more active in counteracting free radicals. Present findings showed that ethanol and chloroform extracts of Lemon peels displayed antimicrobials effectiveness versus S. aureus, P. aeruginosa, and C. albicans, with different degrees of effectiveness. Using ethanol extract the IC50 values for S. aureus was >2500 µg/ml, the IC50 for P. aeruginosa was 838 µg/ml, and for C. albicans was 2194; and when using the chloroform ones the IC50 for S. aureus was 602 µg/ml, the IC50 of P. aeruginosa at 698 µg/ml and IC50 for C. albicans at 482 µg/ml. The chloroform lemon peels extract seems to be more effectual overall compared with ethanol extract based on the IC50 values. Conclusion: The present findings showed that P. aeruginosa is more susceptible to the ethanolic extract than S. aureus and C. albicans. While C. albicans exhibited the lowest IC50 (482 µg/mL), revealing powerful antifungal activity for chloroform extract. Chloroform lemon peels extract seems to be more effectual overall compared with ethanol extract based on the IC50 values.